ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE DALAM MENGOPLIMALKAN PELAKSANAAN SISTEM INFORMASI AKUNTANSI - Halimatusadiah, Elly; Gunwan, Bangun (Program Studi Akuntansi FPEB UPI, 2014)
This research purpose to determine the application of Good Corporate Governance at PT. POS INDONESIA (Persero), to determine the implementation of Accounting Information Systems at PT. POS Indones (Persero), and to determine the application of good corporate governance in order to optimize the implementation of Accounting Information Systems at PT. POS Indonesia (Persero). This research uses descriptive method of analysis which aims to get a fairly clear picture of the object examined. Moreover, the authors use a case study, because the authors only discuss the case and retrieval of data on just one company. This research was conducted at PT. POS INDONESIA (Persero) which is located on Jl. Cilaki No. 73 Bandung. The result showed that the implementation of good corporate governance has been adequate, because it has been supported by the elements of Good Corporate Governance consisting of transparency, accountability, responsibility, independence, equality and fairness, and is supported by the stages full of Good Corporate Governance consists of the implementation phase, implementation phase and the evaluation phase, then Implementation of Accounting Information Systems has been adequate, because the input data has been performed with a high level of accuracy, timely, complete, concise, relevant, reliable and comparable. Data processing has also been carried out in accordance with Financial Accounting Standards.